Changes induced by sucrose administration on glucose metabolism in pancreatic islets in normal hamsters - Massa, María Laura (2001)
We correlated the changes in glucose-induced insulin secretion with those observed in glucose metabolism and hexokinase/glucokinase activity in islets from normal sucrose-fed hamsters. Blood glucose and insulin levels were measured in normal male hamsters fed with (S5) or without (C5) 10% sucrose in the drinking water for 5 weeks. Isolated islets (collagenase digestion) from both groups of animals were used to study insulin secretion, 14CO2 and 3H2O production from D-[U-14C]-glucose and D-[5-3H]-glucose respectively, with 3.3 or 16.7 mM glucose in the medium, and hexokinase/glucokinase activity (fluorometric assay) in islet homogenates. Whereas S5 and C5 animals had comparable normal blood glucose levels, S5 showed higher insulin levels than C5 hamsters (2.3 ± 0.1 vs 0.6 ± 0.03 ng/ml, P<0.001). Islets from S5 hamsters released significantly more insulin than C5 islets in the presence of low and high glucose (3.3 mM glucose: 0.77 ± 0.04 vs 0.20 ± 0.06 pg/ng DNA/min, P<0.001; 16.7 mM glucose: 2.77 ± 0.12 vs 0.85 ± 0.06 pg/ng DNA/min, P<0.001) and produced significantly higher amounts of 14CO2 and 3H2O at both glucose concentrations (14CO2: 3.3 mM glucose: 0.27 ± 0.01 vs 0.18 ± 0.01, P<0.001; 16.7 mM glucose: 1.44 ± 0.15 vs 0.96 ± 0.08, P<0.02; 3H2O: 3.3 mM glucose: 0.31 ± 0.02 vs 0.15 ± 0.01, P<0.001; 16.7 mM glucose: 1.46 ± 0.20 vs 0.76 ± 0.05 pmol glucose/ng DNA/min, P<0.005). The hexokinase Km and Vmax values from S5 animals were significantly higher than those from C5 ones (Km: 100.14 ± 7.01 vs 59.90 ± 3.95 ♂M, P<0.001; Vmax: 0.010 ± 0.0005 vs 0.008 ± 0.0006 pmol glucose/ng DNA/min, P<0.02). Conversely, the glucokinase Km value from S5 animals was significantly lower than in C5 animals (Km: 15.31 ± 2.64 vs 35.01 ± 1.65 mM, P<0.001), whereas Vmax figures were within a comparable range in both groups (Vmax: 0.048 ± 0.009 vs 0.094 ± 0.035 pmol glucose/ng DNA/min, not significant). The glucose phosphorylation ratio measured at 1 and 100 mM (hexokinase/glucokinase ratio) was significantly higher in S5 (0.26 ± 0.02) than in C5 animals (0.11 ± 0.01, P<0.005), and it was attributable to an increase in the hexokinase activity in S5 animals. In conclusion, sucrose administration increased the hexokinase/glucokinase activity ratio in the islets, which would condition the increase in glucose metabolism by β-cells, and in β-cell sensitivity and responsiveness to glucose. These results support the concept that increased hexokinase rather than glucokinase activity causes the β-cell hypersensitivity to glucose, hexokinase being metabolically more active than glucokinase to up-regulate β-cell function.